One year of Donald Tusk’s government: what has changed in Poland? - Oleg Yu. Mikhalev (Научно-аналитический вестник Института Европы РАН)
The objective of this article is to examine the main changes in the Polish economy and domestic policy a year after the formation of the new government. The parliamentary elections of October 2023 ended the eight-year rule of the Law and Justice party and brought the left-liberal coalition to power. On the eve of the elections, it promised substantial changes in the country, but not much has been accomplished in a year. The author points out that the fulfillment of pre-election intentions faced a number of serious obstacles. D. Tusk’s government has not significantly changed its economic course towards reducing the state’s presence in the economy and cutting budget expenditures. On the contrary, it has further increased the budget deficit. So far, its only achievement in this area is the unblocking of funds from Brussels. The restoration of judicial independence, the liberalization of abortion legislation, the legalization of partnerships, the easing of migration policy and other promised reforms have been stalled. The most noticeable changes were only the change in the rhetoric of the mass media, which was rapidly taken out of the control of the Law and Justice party, and the making of numerous allegations against the losing party and its individual members. The author considers disagreements between the parties of the ruling coalition and the resistance of President A. Duda as the primary factors hampering the pace of transformation.